KINERJA DINAS PARIWISATA KOTA BENGKULU DALAM PENGEMBANGAN OBJEK WISATA PANTAI JAKAT PROVINSI BENGKULU - Teddy Surya Rahmadi; Dwi Indah Kartika; AYU WIDOWATI JOHANNES (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2021)
This research aims to describe the performance of the Bengkulu City Tourism Office of Bengkulu Province in the development of Jakat Beach tourism objects, by focusing on the factors that support and hinder, as well as the efforts made in the development of these tourist objects. The method used in this research is descriptive qualitative with an inductive approach. There are also data collection techniques used are interviews, documentation, observation. Meanwhile, the data analysis technique used is data reduction, data display and conclusion drawing. The results of the research are the supporting factors, namely the potential for tourism objects, local government support, and community participation. Factors that hinder the development of Jakat Beach tourism object include the clean environment is still dirty and scattered garbage, tourism supporting facilities and infrastructure that are less well maintained, and the large number of damaged infrastructure. Efforts are being made, namely the arrangement of environmental cleanliness in Jakat Beach tourism, maintaining facilities and infrastructure in the tourist attraction area, as well as repairing and adding infrastructure in the Jakat Beach tourist attraction area. The suggestion from this research is that the Bengkulu City Tourism Office pays more attention to and prepares supporting facilities for the convenience of visitors.